2008
DOI: 10.1007/s00534-007-1246-1
|View full text |Cite
|
Sign up to set email alerts
|

Pneumatosis intestinalis and hepatic portal venous gas

Abstract: We report two cases of pneumatosis intestinalis and hepatic portal venous gas. The first case was in a 67-year-old woman who complained of strong right lower abdominal pain and high fever on the twelfth day after pancreatoduodenectomy (PD) with portal vein (PV) resection. Abdominal X-ray and computed tomography showed hepatic portal venous gas and pneumatosis intestinalis. The emergency laparotomy performed disclosed extensive necrosis of the bowel from the jejunum to the ascending colon. All necrotic parts of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…Portal venous gas has been frequently reported as a concurrent finding when bowel wall ischemia and necrosis are present in human reports and has been suggested in the veterinary literature . Portal venous gas has also been associated with hydrogen peroxide ingestion in a dog .…”
Section: Discussionmentioning
confidence: 98%
“…Portal venous gas has been frequently reported as a concurrent finding when bowel wall ischemia and necrosis are present in human reports and has been suggested in the veterinary literature . Portal venous gas has also been associated with hydrogen peroxide ingestion in a dog .…”
Section: Discussionmentioning
confidence: 98%
“…Aeroportia is more suggestive (although non-pathognomonic) of transmural necrosis than pneumatosis intestinalis, and it carries a worse prognosis [3]. These features cannot guide the search for the cause of ischemia: they may appear with embolic, thrombotic, or low cardiac outflow ischemia, as well as with other diseases [1,4]. Morris et al have recently reviewed 97 patients with pneumatosis intestinalis on the CT scan: approximately one half of patients with pneumatosis intestinalis could be successfully managed non-operatively, but the association of aeroportia conferred a high mortality rate [3].…”
Section: Discussionmentioning
confidence: 96%
“…Much prior experience has indicated that the finding of PI (most especially in association with PVG [3] ) on postoperative imaging in an unwell patient is an ominous sign that should trigger re-exploratory surgery, likely laparotomy [4,5] . However, in other settings, PI is known to have a benign course and the same appearances can be seen in association with steroid or chemotherapy usage, trauma and inflammatory conditions [6] .…”
Section: Discussionmentioning
confidence: 99%